Pyridyl‐Endcapped Polyynes: Stabilized Wire‐like Molecules. (26th October 2016) - Krempe, Maximilian; Lippert, Rainer; Hampel, Frank; Ivanović‐Burmazović, Ivana; Jux, Norbert; Tykwinski, Rik R.
Abstract: A 4‐ethynylpyridyl derivative with sterically shielding phenyl groups in the 3‐ and 5‐positions has been synthesized and used to terminate a series of polyynes. This approach allows for the synthesis of stable polyynes up to an octayne, twice as long as previous accessible for "unstabilized" pyridyl‐endcapped polyynes. The potential of these polyynes as wire‐like linkers to metal centers is demonstrated by axial coordination of pyridyl groups to zinc‐ and ruthenium‐metalloporphyrins.